2021
DOI: 10.1186/s12885-021-09071-1
|View full text |Cite
|
Sign up to set email alerts
|

Mammography screening and mortality by risk status in the California teachers study

Abstract: Background The debate continues among medical professionals regarding the frequency, starting age, and stopping age for mammography screening. Some experts suggest tailoring recommendations based on individuals’ personal breast cancer risk. Previous studies have not compared the impact of annual versus biennial mammography stratified by age group and risk category. The purpose of this study was to examine the relationship between mammography frequency and mortality by age group and risk categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 52 publications
0
12
0
1
Order By: Relevance
“…Of the 27 observational studies, 18 studies followed up women after screening and/or diagnosis; [ 4 , 16 , 21 , 23 , 26 , 32 , 33 , 35 37 , 40 – 43 , 45 , 48 – 50 ] follow-up times in these studies ranged from 4 months to 20 years. Three studies did not include any comparison group and provided only descriptive statistics [ 22 , 24 , 27 ] and three studies compared groups by detection methods in those with breast cancer [ 32 , 33 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 27 observational studies, 18 studies followed up women after screening and/or diagnosis; [ 4 , 16 , 21 , 23 , 26 , 32 , 33 , 35 37 , 40 – 43 , 45 , 48 – 50 ] follow-up times in these studies ranged from 4 months to 20 years. Three studies did not include any comparison group and provided only descriptive statistics [ 22 , 24 , 27 ] and three studies compared groups by detection methods in those with breast cancer [ 32 , 33 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Three studies did not include any comparison group and provided only descriptive statistics [ 22 , 24 , 27 ] and three studies compared groups by detection methods in those with breast cancer [ 32 , 33 , 36 ]. One study had multiple comparisons (by age and screening history) [ 35 ]; the remaining studies compared mammography screening outcomes in women aged 75 years and older with screening outcomes in women: of other ages (ten studies) [ 4 , 16 , 18 , 20 , 21 , 23 , 25 , 38 , 43 , 48 ]; differing screening histories (three studies) [ 44 46 ]; differing screening intervals (three studies) [ 37 , 40 , 41 ] or historical unscreened women (one study) [ 49 ]; women who did not screen (one study) [ 42 ] and women who stopped screening (two studies) [ 26 , 50 ]. (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, adherence to a screening program is a key to achieving a sustainable result with mortality improvement. A study by Park et al found that overall mortality risk was lower for patients with annual compared with biennial mammography [ 19 ]. Further investigation is required to see if similar results would apply to ultrasound-based screening.…”
Section: Discussionmentioning
confidence: 99%